THE IMPACT OF DISCIPLINE ON EMPLOYEE PERFORMANCE AT CENTRAL MALUKU REGENCY’S PERSONNEL AND HUMAN RESOURCES DEVELOPMENT AGENCY (BKPSDM) - Sopamena, Ibrahim Idham; Normawati, Normawati; Pattimukay, Hengky V. R. (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2024)
This study aims to determine the influence of discipline on employee performance at the Personnel and Human Resources Development Agency (BKPSDM) of Central Maluku Regency. The research method used is quantitative, with a sample size of 36 people. The types of data used in this study include primary data and secondary data. Data collection was carried out through literature studies and field studies. Data analysis was conducted using regression analysis tools with the help of SPSS version 20 software. The results of the study show that discipline has a significant influence on employee performance at BKPSDM Central Maluku Regency. Good and consistent discipline can improve overall employee performance. These findings emphasize the importance of implementing strict and systematic discipline in the workplace to achieve optimal performance. Based on regression analysis, there is a positive relationship between the level of discipline and the improvement in employee performance. The implications of these research findings are the need to strengthen the influence of discipline on employee performance at BKPSDM Central Maluku Regency. This can be done through the implementation of more effective disciplinary policies, employee training and development, as well as increased supervision and evaluation of the execution of the duties and responsibilities of employees. Thus, it is expected that employee performance at BKPSDM Central Maluku Regency can continue to improve and provide a positive contribution to the achievement of organizational goals.